Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Memulai Kepuasan Kerja Pada PT. Bumi Sentosa Dwi Agung - Lesmana, Fadli; Idris, Idris; Asiati, Diah Isnaini (MOTIVASI, 2019)
Purpose - This study aims: (1) to determine the effect of leadership style and job environmenton job satisfaction at Bumi Sentosa  Dwi Agung, Ltd, (2) To determine the effect of leadership style and job environmentonemployee performance at Bumi Sentosa  Dwi Agung, Ltd,(3) to determine the effect of leadership style and job environmenton employee performance  through  job satisfaction at  Bumi Sentosa.Design/methodology - The research design used in this study is associative. The variables used were ndependent variables are Leadership Style (X1) and Job Environment (X2), the intervening  variables is Job Satisfaction (Y), and the dependent variables is Employee Performance (Z). Data collection technique used documentation and questionnaires. The population in this study as much as 150 employees, analytical techniques used are cluster sampling, so that the sample used as much as 110 employees. The analytical method using Path Analysis. Findings - Based on the findings that: (1) There is a positive and the significant effect of leadership style and job environment on the job satisfaction at Bumi Sentosa Dwi Agung, Ltd, (2) There is a positive and the significant effect of leadership style, job environment, and job satisfaction on the employee performance at Bumi Sentosa Dwi Agung, Ltd, and (3) There is a positive but not significant effect of leadership style and job environment on employee performance through the job satisfaction at Bumi Sentosa Dwi Agung, Ltd.